Analysis of temperature and humidity variation in the pre-rainy season in the city of Sobral (Research, Society and Development, 2021)
This article aims to analyze the variability of temperature and relative humidity during the pre-rainy season in a semi-arid environment. For this, data related to these climatic elements were collected through mini dataloggers housed in PVC structures installed in five sample points throughout the city of Sobral/CE. The research was guided by the theoretical assumptions defined by Carlos Augusto de Figueiredo Monteiro, who defined a theoretical and methodological framework for understanding the urban factor, through the Urban Climate System (SCU). The data correspond to three days of uninterrupted hourly collections. Our results show an unusual performance by ZCIT, which directly interfered in the results, through an increase in precipitation and cloud cover. We also found that, for the studied period, temperatures were always high, although they showed variability, as well as the relative humidity of the air. In the end, one of the most striking characteristics of the semiarid region of northeastern Brazil is evident, high temperatures.